Malaysian graduates’ employability skills enhancement: an application of the importance performance analysis - Abdul Hamid, Mohamad Shukri; Islam, Rafikul; Abd. Manaf, Noor Hazilah (2014 Inderscience Enterprises Ltd. , UK, 2014)
In an era of globalization and competitiveness, employers are looking for versatile graduates who are able to drive their organizations to compete successfully in the marketplace. Now-a-days, obtaining a good degree is no longer sufficient to get a job. Graduates should equip themselves, not only with technical skills, but more importantly, with soft skills. The main objectives of this study are to identify Malaysian graduates’ employability skills, to identify the priority of each skill and to highlight the gap between the importance of graduates’ employability skills to employers and their level of satisfaction on those skills. In general, the results of the gap analysis showed that employers perceive graduates’ employability skills performance as being lower than the importance assigned to those skills. The widest gap was found in communication skills, especially the skill of the English language usage. Using the Importance-Performance Analysis (IPA), 13 attributes fell into the improvement quadrant. This means that improvement efforts and corrective actions must be taken to improve employers’ overall satisfaction level.